Seguaci americani della Scuola Romana di fotografia: Nathan Flint Baker, Leavitt Hunt e Richard Morris Hunt - Saunders, Beth (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
In 1851, before embarking on a journey to Egypt and the Near East, Americans Leavitt Hunt (1831-1907) and Nathan Flint Baker (1820-1891) traveled to Rome to learn photography. There, they encountered members of the Roman School, an international group of practitioners of paper negatives. A year later, Leavitt’s brother Richard Morris Hunt (1827-1895) traveled to the same sites and collected photographs. This article explores the networks that connected them to Rome, illuminating a little-known American contribution to paper photography and providing further confirmation of the influence of the Roman School on the medium’s development.